Taking sides : using taking sides in the classroom. (Guilford, Conn. : Dushkin Pub. Group/Brown & Benchmark Publishers, 1996)
Methods, systems, and techniques of teaching controversial issues.
"Methods, systems and techniques for the teaching of controversial issues"--Cover.
Keywords: Debates and debating -- Study and teaching; Discussion -- Study and teaching; Social sciences -- Study and teaching; Debates and debating -- Study and teaching; Discussion -- Study and teaching; Social sciences -- Study and teaching